Experiences of Microfinance Institutions Serving Very Small to Small Enterprises in Latin America : Based on Case Studies in LAC - International Finance Corporation (Washington, DC, 2015)
Very small enterprises (VSEs) in Latin America and the Caribbean (LAC) represent a broad and heterogeneous segment, often underserved by formal financial institutions. They are generally informal and often family businesses. The financial needs of these enterprises are typically overlooked by “downscaling” banks, which find larger and often more formal small and medium enterprises (SMEs) to be a more natural market for their products and services. Microfinance Institutions (MFIs) are starting to move upmarket to serve SMEs, and in particular, VSEs within this segment. However, they use varying definitions, methodologies and products to do so and to date there has been little research or documentation of their experiences. This report highlights the results of a recent study of the existing practices in Latin America of MFIs serving VSEs, where VSEs are considered to be those businesses with financing needs of between US$7,000 and US$30,000. It is a starting point for an institution considering entering the segment, or for one that finds itself having grown into the segment “organically” but with a view to strengthen its position. It includes several checklists for MFIs interested in expanding upmarket into the VSE space, as well as more detailed discussions and examples of the most relevant points.